Mediterranean Connections How the sea links people and transforms identities - Schmidt, Laura C.; Rutter, Anja; Käppel, Lutz; Nakoinz, Oliver (Scales of Transformation, 2023)
The present publication constitutes the Proceedings of Session 7 of the 'Creation of landscapes VI' workshop, hosted by the CAU Kiel in 2019. The session was entitled 'Mediterranean Connections - how the sea links people and transforms identities'. With our focus on the linkage of people, this volume can be understood as a contribution to recent network research. But network research, especially when employed in the humanities, is often looked at with scepticism, not to say mistrust: Isn't this just a game with numbers? Does it really relate to the type of data we are used to in our research, to poems, sherds or seal impressions? Can it say anything at all about... life? In fact, the various articles of this volume are not restricted to the strict technical approach of classical network research. Our session on Mediterranean networks started from the idea that for the inhabitants of this relatively integrated region, the sea evidently influenced their lives and their thinking in a significant way. In fact, it was the sea that provided the medium for such integration on various levels. The substantial body of data produced by long-standing research in diverse disciplines makes it possible to chart the emergence of ancient perceptions of distance and movement, connectivity and identities. This approach allows us to observe ancient awareness of the role of the sea in these processes. It also allows us to connect across academic boundaries and build a network of disciplines for a much more cohesive picture of past life.